UPAYA PENINGKATAN KESADARAN MASYARAKAT TENTANG TUBERKULOSIS DAN KEPATUHAN MINUM OBAT PADA PENDERITA TUBERKULOSIS DI NAGARI PIANGGU KABUPATEN SOLOK - Azrimaidaliza Azrimaidaliza; Aulia Rahma Septiadi; Nuri Setiani; Ogid Meisi Ludipa; Haptiah Haptiah; Wenny Dwiwardani; Penia Resty (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
The prevalence of tuberculosis (TB) has increased from 2018, which is recorded 10,000,000 cases of tuberculosis (5,800,000 men and 3,200,000 women) in the worldwide. Indonesia is among the three countries with the highest prevalence of tuberculosis in the world in 2018. The problem obtained from the results of the Healthy Family Indicator survey in Nagari Pianggu is the low percentage of TB patients who seek medical treatment regularly by 35%. This activity aims to increase public awareness about TB and medication adherence to TB sufferers. The activity was carried out using the PDCA (Planning Do Check Action) approach. The activity begins with problem identification, planning, implementation of activities, monitoring and evaluation. The activity was carried out in accordance with the plan, namely in Nagari Pianggu, Sungai Lasi Health Centre Work Area. The results obtained from this activity are the implementation of problem identification activities, determining problems and causes, determining alternative solutions to problems, intervening, compiling monitoring and evaluation plans. Intervention activities in the form of counselling about TB and the distribution of health promotion media went smoothly and it was also recommended that TB sufferers continue treatment until it was completed so that TB problems could be overcome.